MET alterations in advanced pulmonary sarcomatoid carcinoma - Gong, Chen; Xiong, Huihua; Qin, Kai; Wang, Jianhua; Cheng, Yi; Zhao, Jing; Zhang, Jing (Frontiers in Oncology, 2022)
PPulmonary sarcomatoid carcinoma (PSC) is a rare subset of NSCLC that accounts for about 0.5-1% of all primary lung carcinoma, and its malignant biological behavior is more aggressive than other pathological types of lung cancer. Recent studies have reported a variety of gene mutations associated with the occurrence, development and treatment of PSC, especially the mesenchymal-epithelial transition (MET) proto-oncogene alterations, including the exon 14 (METex14) skipping mutations as well as the amplification and overexpression of MET gene, which are associated with molecularly targeted therapy for PSC. METex14 skipping mutation is the most common and well-studied mutation type, occurring in about 22-31.8% of PSC patients, while the prevalence of MET amplification is reported as 4.8-13.6% and MET ovexpression is about 20.2%. Molecular pathology tests, including IHC and NGS, are valuable in determining the prognosis of patients with PSC and helping to determine the treatment. The existing clinical data have confirmed the efficacy of MET-TKI in PSC patients with MET alteration, among which the clinical study of Savolitinib has enrolled the largest proportion of PSC patients and achieved relatively good efficacy, but more clinical researches are still needed. The multi-disciplinary team may maximize the optimal treatment options for patients with the advanced PSC.